PEDAGOGICAL AND THEORETICAL BASIS OF FORMING CRITICAL THINKING IN STUDENTS - Tokhtamysheva Maftuna Khursanovna (Modern American Journals, 2025)
This article examines the main stages of the formation of theoretical and critical thinking. The goals and objectives of the formation of critical and creative thinking in students, the pedagogical and psychological aspects of critical and creative thinking, taking into account the age and capabilities of students, were considered.
Keywords: Thinking, social order, critical thinking, types of thinking, creative thinking, intellectual potential.